2011
DOI: 10.4049/jimmunol.1000955
|View full text |Cite
|
Sign up to set email alerts
|

Chemoattractant-Induced Signaling via the Ras–ERK and PI3K–Akt Networks, along with Leukotriene C4 Release, Is Dependent on the Tyrosine Kinase Lyn in IL-5– and IL-3–Primed Human Blood Eosinophils

Abstract: Human blood eosinophils exhibit a hyper-active phenotype in response to chemotactic factors following cell “priming” with IL-5 family cytokines. Earlier work has identified ERK1/2 as molecular markers for IL-5 priming, and herein we show that IL-3, a member of IL-5 family, also augments fMLP-stimulated ERK1/2 phosphorylation in primary eosinophils. Besides ERK1/2, we also observed an enhancement of chemotactic factor-induced Akt phosphorylation following IL-5 priming of human blood eosinophils. Administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 80 publications
2
29
0
Order By: Relevance
“…In eosinophils treated with IL-5 for 60 minutes, a subsequent 3-minute treatment with fMLF induced ERK phosphorylation in almost all cells, with the same pERK distribution as in eosinophils treated with IL-5 for 10 minutes (compare Figures 7A and 7B). These data corroborate published Western blotting results indicating that a 60-minute incubation with IL-5 renders the eosinophils more sensitive to subsequent stimulation with fMLF (24,25), even though ERK phosphorylation has returned to basal level at this time point (26).…”
Section: Eosinophil Polarization Is Associated With Enhanced Erk Phossupporting
confidence: 91%
See 2 more Smart Citations
“…In eosinophils treated with IL-5 for 60 minutes, a subsequent 3-minute treatment with fMLF induced ERK phosphorylation in almost all cells, with the same pERK distribution as in eosinophils treated with IL-5 for 10 minutes (compare Figures 7A and 7B). These data corroborate published Western blotting results indicating that a 60-minute incubation with IL-5 renders the eosinophils more sensitive to subsequent stimulation with fMLF (24,25), even though ERK phosphorylation has returned to basal level at this time point (26).…”
Section: Eosinophil Polarization Is Associated With Enhanced Erk Phossupporting
confidence: 91%
“…IL-5 family cytokines also prime eosinophils to react with increased release of granule proteins, increased production of leukotriene C4, and chemotaxis on subsequent stimulation with other activators (42)(43)(44)(45)(46). fMLF induces greater ERK phosphorylation, as analyzed by Western blotting, in IL-5-primed eosinophils than in unprimed cells (25). Polarization of eosinophils is accompanied by distribution of ERK to the granular compartment as well as to the nucleopod tip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…85 Interestingly though, after 1 hour of activation, IL-3 and IL-5 have a very comparable strength to prime eosinophils in order to respond to a second activation with a ligand to a G protein-coupled receptor. 95 Unlike for a short-term activation, long-term cytokine activation of eosinophils substantially changes the potential of the three βc family cytokines on eosinophil signaling. We have shown that IL-3 activation leads to a prolonged (> 48 h) phosphorylation of the ribosomal protein S6 (RPS6), downstream of p90S6K (RSK) and ERK phosphorylations, while IL-5 and GM-CSF could not maintain this intracellular signaling for more than a few hours.…”
Section: Differential Protein Translation Of Semaphorin-7a and CDmentioning
confidence: 99%
“…Basic FGF, EGF, PDGF, insulin-like growth factor-1 (IGF-1), and insulin all induce airway smooth muscle cell proliferation and seem to play a role in the hyperproliferation aspect of asthma (101). Nonreceptor tyrosine kinases like Lyn are also involved in the inflammatory component of asthma: Leukotriene C4 release depends on Lyn kinase in IL-5-and IL-3-primed human blood eosinophils, which infiltrate the airways and are key players in asthma (102). Interestingly, Pyk2 (103) and Tie2 (104) were also found to play a role in a mouse asthma model.…”
Section: Asthma and Tyrosine Kinase Inhibitorsmentioning
confidence: 99%